The magnetorheological fluid: testing on automotive braking system - Zainordin, Ahmad Zaifazlin; Mohamed, Zamri; Ahmad, Fauzi (Penerbit Universiti Malaysia Pahang, 2021)
This paper presents testing of the magnetorheological brake (MRB) in the braking system of a vehicle. Two techniques are used to determine the capability of the brake system, which are simulation via Matlab Simulink Software and experimental study by using a quarter vehicle test rig. A Proportional-Integral-Derivative (PID) is employed as a wheel speed control and enforces the MRB to produce the required braking torque need by a vehicle. A dynamic test, namely sudden braking test, is performed in three rotational speed conditions, which are from 127.5 rad/s (1200 rpm) to 31.42 rad/s (300 rpm), 52.37 Rad/s (500 rpm) and 73.31 rad/s (700 rpm) in two different wheel load which are 10 kg and 15 kg, respectively. The behaviours to be assessed are wheel speed response and brake torque produced by the MRB. From the observation, the MRB’s capability in providing the required brake torque is promising and harmony between simulation and experimental response.